Processing of Voiced and Unvoiced Acoustic Stimuli in Musicians - Ott, Cyrill G.; Langer, Nicolas; Oechslin, Mathias S.; Meyer, Martin; Jäncke, Lutz (Frontiers in Psychology, 2011)
Past research has shown that musical training induces changes in the processing of supra-segmental aspects of speech, such as pitch and prosody. The aim of the present study was to determine whether musical expertise also leads to an altered neurophysiological processing of sub-segmental information available in the speech signal, in particular the voice onset time (VOT). Using high-density EEG recordings we analysed the neurophysiological responses to voiced and unvoiced CV syllables and noise analogues in 26 German speaking adult musicians and non-musicians. From the EEG the N1 amplitude of the event-related potential (ERP) and two microstates from the topographical EEG analysis (one around the N1 amplitude and one immediately preceding the N1 microstate) were calculated to the different stimuli. Similar to earlier studies the N1 amplitude was different to voiced and unvoiced stimuli in non-musicians with larger amplitudes to voiced stimuli. The more refined microstate analysis revealed that the microstate within the N1 time window was shorter to unvoiced stimuli in non-musicians. For musicians there was no difference for the N1 amplitudes and the corresponding microstates between voiced and unvoiced stimuli. In addition, there was a longer very early microstate preceding the microstate at the N1 time window to non-speech stimuli only in musicians. Taken together, our findings suggest that musicians process unvoiced stimuli (irrespective whether these stimuli are speech or non-speech stimuli) differently. We propose that musicians utilise the same network to analyse unvoiced stimuli as for the analysis of voiced stimuli. As a further explanation it is also possible that musicians devote more neurophysiological resources into the analysis of unvoiced segments.